Keefektifan Bakteri Endofit untuk Mengendalikan Nematoda Parasit Meloidogyne Incognita pada Tanaman Lada - Abdul Munif; Rita Harni (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The utilization of biological agents for controlling plant diseases was increased along with the hazards of pesticide use and awareness on the environmental friendly farming. The objective of this study was to determine the effect of endophytic bacteria on yellow diseases on pepper caused by plant parasitic nematodes Meloidogyne incognita. Endophytic bacteria that used in this study were isolated from roots of black pepper plants and some of selected endophytic bacteria collection from Department of Plant Protection, IPB and Research Institute for Spice and Industrial Crops. The results showed that some endophytic bacteria are able to promote the growth of pepper seedlings and also reduce the root gall caused by Meloidogyne spp and juveniles of nematodes in the soil up to 90% and increase the growth of pepper plants.